Role of the team’s administrative supervisor in providing safety factors in training from the perspective of the players of the Iraqi Premier League futsal clubs - Hamed al-Dulaimi, Thakir Mahfoudh; Rafeeq, Shaheen Ramzi; Ismail al-Asharifi, Riadh Ahmed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to determinate the level of perception of the role of the team’s administrative supervisor in providing safety factors in the training units from the perspective of players of the Iraqi Premier League futsal clubs, as well as developing a proposal for this role. A cross-sectional design was used in this study. The research community included 279 players representing 16 clubs of the Iraqi Premier League of futsal, while the final sample consisted of 126 players. To obtain the data, a questionnaire was designed to propose the role of the team’s administrative supervisor in providing safety factors in the training units according to three dimensions: supporting the training requirements, supporting the requirements of sports medicine, and supporting supportive services. Based on the players’ perspective about the role of the team’s administrative supervisor in providing safety factors in training units, the results of the study show us that the overall result of the first dimension (supporting the training requirements) reached a high level of 77% with an arithmetic mean of 38.615. The overall result of the second dimension (supporting the requirements of sports medicine) reached a high level of 76% with an arithmetic mean of 38,423, and the overall result of the third dimension (supporting supportive services) also reached a high level of 77% with an arithmetic mean of 38.715. The research revealed that the teams’ administrative supervisors of the Iraqi Premier League Futsal Clubs can play an active and positive role in providing the safety factors in the training units from the perspective of the players of these teams, according to the dimensions of supporting the requirements of training, sports medicine services and other supportive services.